Symbols and Values in the Traditional Wedding Ceremony Baralek Kosik in Sungai Aur District, West Pasaman Regency, West Sumatra Province - Syafitri, Yesi; Efi, Agusti (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
The traditional wedding Baralek is the result of the culture and traditions of the people in Sungai Aur District, West Pasaman Regency, West Sumatra Province. This study aimed to explain the Baralek Adat Kosik in Sungai Aur District. Baralek Adat Kosik is one of the traditional weddings prevailing in Nagari Sungai Aur. This study used a qualitative method. Research data were collected from several informants, such as ninik mamak, puti adat, and community leaders. This research was focused on: the procession of the ceremony Baralek Adat Kosik, the traditional symbols in the Baralek Adat Kosik as a means of cultural activity in the ceremony Baralek Adat Kosik in Nagari Sungai Aur, and the values ​​contained in the ceremony Baralek Adat Kosik in Nagari Sungai Aur. The findings of this study were that the procession of Baralek Adat Kosik in Sungai Aur District had a series of processions of Duduk Ninik Mamak, Koun-Koun, Bokayu, slaughter Kambiang, Bokureh Cooking, Monyambut Marapulai, Baarak Tamat Kaji, Tamat Kaji, Baarak Gadang, and Monutup Olek. In the traditional ceremony Baralek Kosik, there are several traditional symbols, namely, Kambiang, Marawa, Carano, Tabie, Bokayu, Manyirak Bareh dan Kunyit, Caranobaki, Anak Daro and Marapulai’s Umbrella, Khatam Al-Quran, Dike-e, Nasi Sojamba Kunyik, and Ayam Panggang Soikuo. These traditional symbols contain sacred values, religious values, moral values, entertainment values, and social values. All this is summarized in the procession Baralek, custom symbols, and values contained in Baralek Kosik custom.